2
$\begingroup$

Here's the original equation:

$\ln(11x-10) + \Big(\ln(11x-10)\Big)^2$ = 6

I've managed to obtain one solution: $x = \frac{e^2 + 10}{11}$

through those steps:

  1. $\ln\Big((11x-10)(11x-10)^2\Big) = 6$

  2. $\ln\Big((11x-10)^3\Big) = 6$

  3. $(11x-10)^3 = e^6$

  4. $11x-10 = e^2$

  5. $11x = e^2+10$

  6. $x = \dfrac{e^2+10}{11}$

The textbook shows a second solution: $x = \dfrac{10e^3 + 1}{11e^3}$, but how do you get to that result?

$\endgroup$
1
  • $\begingroup$ Your original equation has the form $y^2+y=6$, which is a quadratic with two solutions for y. $\endgroup$ May 18 '12 at 11:44
2
$\begingroup$

Your solution is incorrect because :

$\ln(11x-10) +(\ln(11x-10))^2$ is not equal to $\ln(11x-10 \times {(11x-10)}^2)$

To solve

$$\ln(11x-10) + (\ln(11x-10))^2 = 6$$

Let $t=\ln(11x-10)$

$$t^2 +t -6=0$$

this gives , $t=2$ and $t=-3$

when $t=2 \longrightarrow \ln(11x-10)=2 \longrightarrow x=\frac{e^2+10}{11}$

when $t=-3 \longrightarrow \ln(11x-10)=-3 \longrightarrow x=\frac{10e^3+1}{11e^3}$

$\endgroup$
0
1
$\begingroup$

Hint: Let $a = \ln(11x - 10)$. Then you would have $$ a + a^2 =6 \qquad \text{or}\qquad a^2 + a -6 =0.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.